FINANCING LIFE INSURANCE and the CONCEPT of MITIGATING THE RISK of CUSTOMER DEATH - khabib musthofa, Khabib Musthoa; nafidzi, elman; maharani, dewi; royzak, abdul (Tawazuna, 2023)
The existence of financing in Islamic banking has several financing risks, one of which is the default of the customer due to death. Facing this risk, banks certainly have risk management so that this can be controlled which in the future does not make Islamic banking suffer losses. In writing this article using a descriptive qualitative approach with a literature study, with the aim of describing the existence of life insurance in financing, risk mitigation and the benefits therein. The strategic step to mitigate risk that is most often used by banks is to provide financing life insurance cover as protection against financing in the face of this disaster, where the existence of insurance is a tool to bear customer financing obligations and as an action so as not to burden other heirs, if examined together there are two substances so that both parties (banks and customers) feel protected.